Mitochondrial-targeted plastoquinone therapy prevents early onset muscle weakness that occurs before atrophy during ovarian cancer - Luca J. Delfinis; Shahrzad Khajehzadehshoushtar; Luke D. Flewwelling; Nathaniel J. Andrews; Madison C. Garibotti; Shivam Gandhi; Aditya N. Brahmbhatt; Brooke A. Morris; Bianca Garlisi; Sylvia Lauks; Caroline Aitken; Leslie Ogilvie; et al. (Molecular Metabolism)
Objective: Muscle loss with cancer causes weakness, worsens quality of life, and predicts reduced overall survival rates. Recently, muscle weakness was identified during early-stage cancer before atrophy develops. This discovery indicates that mechanisms independent of muscle loss must contribute to progressive weakness. While mitochondrial stress responses are associated with early-stage ‘pre-cachexia’ weakness, a causal relationship has not been established. Methods and Results: Here, using a mouse model of metastatic ovarian cancer cachexia, we identified that the well-established mitochondrial-targeted plastoquinone SkQ1 partially prevents muscle weakness occurring before the development of atrophy in the diaphragm. Furthermore, SkQ1 improved force production during atrophy without preventing atrophy itself in the tibialis anterior and diaphragm. These findings indicate that atrophy-independent mechanisms of muscle weakness occur in different muscle types throughout ovarian cancer. Ovarian cancer reduced flexor digitorum brevis (FDB) whole muscle force production and myoplasmic free calcium ([Ca2+]i) during contraction in intact single muscle fibers, both of which were prevented by SkQ1. Remarkably, changes in mitochondrial reactive oxygen species and pyruvate metabolism were heterogeneous across time and between muscle types which highlights a considerable complexity in the relationships between mitochondria and muscle remodeling throughout ovarian cancer. Conclusions: These discoveries identify that muscle weakness can occur independent of atrophy throughout ovarian cancer in a manner that is linked to improved calcium handling. The findings also demonstrate that mitochondrial-targeted therapies exert a robust effect in preserving muscle force early during ovarian cancer during the pre-atrophy period and in late stages once cachexia has become severe.